A GENERAL MODEL OF PARAGLACIAL LANDSCAPE RESPONSE - Ballantyne C.K. (My University, 2002)
A unifying attribute of all forms of paraglacial response is that deglaciation results in the exposure of unstable or metastable sediment sources that are subsequently tapped by a wide variety of processes over a wide range of timescales. The ‘paraglacial period’ in different geomorphological contexts is therefore con ditioned by two variables: glacially conditioned sediment release and rate of sediment reworking. Under steady-state conditions, the latter may be approximated by an exhaustion model in which sediment yield is related to the amount of remaining ‘available’ sediment by a negative exponential function. This model offers an approximation for the behaviour of primary paraglacial systems in which glacigenic sediment sources are not replenished. The long-term behaviour of secondary (primarily ‘ uvial) paraglacial systems in which sediment inputs include both in situ and reworked glacigenic sediment appears intrinsically more complex, but consistent with an exhaustion model if initial sediment availability is greatest in upland tributary basins and declines as A unifying attribute of all forms of paraglacial response is that deglaciation results in the exposure of unstable or metastable sediment sources that are subsequently tapped by a wide variety of processes over a wide range of timescales. The ‘paraglacial period’ in different geomorphological contexts is therefore con ditioned by two variables: glacially conditioned sediment release and rate of sediment reworking. Under steady-state conditions, the latter may be approximated by an exhaustion model in which sediment yield is related to the amount of remaining ‘available’ sediment by a negative exponential function. This model offers an approximation for the behaviour of primary paraglacial systems in which glacigenic sediment sources are not replenished. The long-term behaviour of secondary (primarily ‘ uvial) paraglacial systems in which sediment inputs include both in situ and reworked glacigenic sediment appears intrinsically more complex, but consistent with an exhaustion model if initial sediment availability is greatest in upland tributary basins and declines as catchment size increases. In all paraglacial systems, however, the temporal pattern of sediment release is sensi tive to external perturbation, which has the effect of prolonging and/or rejuvenating sediment release, and may result in renewed paraglacial sediment release millennia after termination of the initial (deglacial) period of paraglacial activity.
Keywords: PARAGLACIAL; DEGLACIATION; EXHAUSTION MODEL; SEDIMENT RELEASE; EXTRINSIC PERTURBATION; LANDSCAPE; INSTABILITY